The influence of interpersonal interaction on consumers’ purchase intention under e-commerce live broadcasting mode: The moderating role of presence - Ma, Xiaoli; Jin, Junna; Liu, Yunrun (Frontiers in Psychology, 2023)
The purpose of this study is to examine the links between consumers' perceptions of interpersonal interaction, perceived value, and intention to purchase in China e-commerce live broadcasting. The mediating effect of perceived value on the relationship between consumer-anchor interaction(CAI) and consumer-consumer interaction(CCI) and purchase intention is explored. Additionally, the moderating effect of presence on the relationship between perceived value and interpersonal interaction perceptions is also investigated. The Hayes' Process macro was utilized as an analysis tool, and the data were gathered via an online survey. We found that both types of interpersonal interaction perceptions are important in creating perceived value and purchase intention,perceived value enhances purchase intention,and presence acts as a moderator in the relationship between consumer perceived value and perceptions of interpersonal interactions, making this relationship stronger when presence is high and weaker when presence is low. In this way, the results of the study will contribute to the current literature of interpersonal interaction under the mode of e-commerce live broadcasting. Employing interpersonal interaction techniques to improve consumers' perceptions of value and purchase intent will also be advantageous to businesses engaging in live e-commerce broadcasting.